Knowledge of blood transfusion among nurses. Issue 17 (25th July 2012) - Hijji, Belal; Parahoo, Kader; Hussein, Mohammad Moshaddeque; Barr, Owen
<x xml:space="preserve">Abstract</x> Aims and objectives. To measure nurses' knowledge of blood transfusion in the United Arab Emirates. Background. Blood transfusion is a fundamental aspect of nursing practice and nurses' knowledge of it is essential for safe practice. Yet little is known about their blood transfusion practice and the knowledge that underpins it. The few studies that have investigated this topic previously have shown deficiencies in both knowledge and practice. To date, no such study has been carried out in the Middle East. Designs. A descriptive, cross‐sectional study. Methods. A random sample of 248 nurses from two general hospitals in the Emirate of Abu Dhabi. The response rate was 94AE3%. A knowledge questionnaire comprising six sections and 49 items was developed for this study. Data were analysed using descriptive and inferential statistics. Results. The overall knowledge scores of nurses were generally low ranging from 27–56 of a possible score of 70. Data analysis revealed knowledge deficits in several key aspects of blood transfusion. There were statistically significant relationship between nurses' knowledge and the work setting, the country where they trained and type of qualifications. Conclusion. This survey highlighted knowledge deficits which could be detrimental to patient safety. These results have implications for nursing education, policy and practice. Relevance to clinical practice. Nurses have the responsibility to update their knowledge of and skills in carrying out blood transfusion. The tool developed in this study may be useful for educators and managers to identify gaps in knowledge and inform decisions to address them.